Synthetic Cannabinoids: A Bibliometric Analysis - Murat Kamalak; Abuzer Gülderen; Muhammed Emin Parlak (Turkish Journal of Forensic Medicine, 2026)
Aim: Synthetic cannabinoids (SC) are one of the fastest-spreading and most concerning classes of new psychoactive substances. Originally synthesized for scientific research, these compounds have rapidly begun to be abused due to their potent psychoactive effects. Compared to Δ9-tetrahydrocannabinol (THC), most SC act as full agonists at cannabinoid receptors, thereby increasing potency and toxicity. The aim of this review is to provide information on the rapidly spreading use of synthetic cannabinoids, including their epidemiology, chemical diversity, pharmacodynamics, pharmacokinetics, and clinical outcomes, and to shed light on the trends in SC research by conducting a bibliometric analysis of original articles and reviews published in the Web of Science. Methods: Electronic literature search was conducted in the electronic literature using the keywords “synthetic cannabinoids, synthetic cannabinoid epidemiology, synthetic cannabinoid pharmacodynamics, pharmacokinetics, and clinical effects” for the review. Articles written in languages other than English and Turkish were excluded from the study. For the bibliometric analysis, data obtained by searching Web of Science using the operator ‘synthetic cannabinoid*’ OR ‘synthetic cannabinoid receptor agonist*’ OR ‘SCRA’ were analyzed using the WOSviewer application. Results: The analysis revealed that synthetic cannabinoids continue to emerge with new compounds and that their prevalence is increasing. The number of publications related to synthetic cannabinoids has shown an upward trend in recent years, supported by the data.Conclusion: Synthetic cannabinoids, which have become a significant health issue due to their increasing use.